Positive column contraction of the glow discharge in nitrogen - Lisovskiy, V.A.; Derevianko, V.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2017)
This paper studies the diffuse mode of the positive column in nitrogen, the contracted one near the threshold of its onset as well as the transition between these modes. The dynamics of the reduced electric field E/p variation as well as that of the electron temperature Te and the plasma concentration are investigated with a Langmuir probe in the process of this transition. The diffuse mode is observed at low pressure in the total range of discharge current values as well as at the pressure values above the threshold one of 1.5 Torr and low current values. The contracted mode sets on at the pressure values above 1.5 Torr. A jump-like transition occurs between the diffuse mode (with low E/p and Te) and the contracted one when a critical current value is attained.